THE MODEL OF PUBLIC INFORMATION OPENNESS: Interactive Broadcast of Memorandum of Understanding (MoU) between Blitar Government and Village Government in the Supervision of the Village Fund Allocation’s Implementation - Yefi Dian Nofa Harumike; Anam Miftakhul Huda (Universitas Islam Balitar, 2018)
This research aims to provide information to the society related to the information openness and transparency of Blitar Government and Village Government in the implementation of Memorandum of Understanding (MoU) of Village Fund Allocation. Several issues stated in MoU include safety and orderliness, action, investigation, apparatus source, society protection, and connection. Other issues include prevention, supervision, and security of village fund. This research employed qualitative method with descriptive approach. The data were obtained from the document of interactive dialog broadcast named “Hallo Bupati– aired by Local Public Broadcast Department (LPPM) radio, Persada FM, Blitar, edition of Monday, January 23, 2018. The informant of this interactive dialog program was the Regent of Blitar. Data analysis was performed by transcribing the broadcast document, organizing and analyzing data, and interpreting the findings.Â The result showed that all the village governments getting Village Fund Allocation in Blitar have madeMemorandum of Understanding (MoU) with the Regent and the Chief Police Officer of the Regency Then, it was followed by supervision and evaluation towards the expenditure of the fund in village level.